Pelatihan Penanggulangaan Kegawatdaruratan Bagi Masyarakat di Desa Curah Cottok, Kapongan, Situbondo, Jawa Timur - Kristina Pae; Ira Ayu Maryuti; Made Indra Ayu Astarini; Andrew Joewono (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Emergency conditions can occur anywhere and anytime. Medical personnel have an obligation to help deal with this situation, even though it is not uncommon for emergencies to occur in areas that are difficult for medical personnel to reach. Community participation in overcoming this situation before it is handled by the medical team is very important. One of the keys to the success of emergency relief is the provision of assistance from the community, which is the first element in finding the victim. The only health facility in Curah Cottok Village is the Primary Health Center (Puskesmas), which is five kilometers away and medical personnel are rarely available. The aim of health education in this community service activity is to increase the knowledge of the people of Curah Cottok Village and their role in handling emergencies. This activity was attended by 30 cadres and village officials. The methods used are lectures, demonstrations, and discussions. Pre-test and post-test is done by filled the questionnaire. Results: There were differences in the results of the correct answers pre and post the emergency management training. The increase is between 3 and 5 points. Conclusion: After training in emergency management, the community's knowledge has increased.